Are professional road cycling countries selecting their talents based on anthropometric characteristics which suit the countries` terrain? - Voet, J.G.; Lamberts, R.P.; de Koning, J.J.; van Erp, T. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND This study investigates if countries are more focused on certain specializations (one day, climb, sprint, time trial [TT] and grand tour [GC]) in male professional road cycling and if this is possibly linked to the countries landscape (for example, does a mountainous country have more climbers?) and anthropometric characteristics (does the mountainous country also have lighter cyclists?) of their cyclists.